PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI DI SMA NEGERI MATAWAI LA PAWU - Hara, Marlince Kariri; Bano, Vidriana Oktoviana; Enda, Riwa Rambu Hada (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to improve student learning outcomes by applying the problem based learning (PBL) learning model to plantae material. This type of research is a class action research (CAR). The subject of this research is class X IPA student at SMA Negeri Matawai La Pawu students’cognitive learning outcomes were measured using the pretest and posttest cycle I and cycle II. Affective learning outcomes are measured using observation sheets. The results showed that the application of the problem based learning (PBL) learning model could improve student learning outcomes. Based on the research results obtained the percentage of student learning outcomes in cycle I pretest value 0f 45%, posttest value of 75%, nand cycle II pretest value 35% and posttest value 90%. Affective learning outcomes tn the first cycle,the result for the low category were 60% the medium category was 20%, while the high category was 20%. In cycle II, the result for the low category were 0%, the medium category was 20%, while the high category was 80%. The conclusion obtained from this study is that the application of the problem-based learning model can improve learning outcomes for class X IPA at SMA Negeri Matawai La Pawu.